Effect of a non-circular shape of the torus on the l=2 torsatron magnetic surfaces - Kotenko (Вопросы атомной науки и техники, 2017)
The numerical calculations of magnetic field of the l=2 torsatron magnetic system with non-circular poloidal cross-section of the torus is carried out in the work. It is shown that the value δi≈0.2 of maximal relative deviation of a non-circular poloidal cross-section from basic circular one results in a several-fold contraction of closed magnetic surface existence region. There is some increase in the values of rotational transform angle and the mirror ratio in the central closed magnetic surfaces. An enlarged clearance between the outer boundary of field line stochastic layer, i.e., the boundary of the plasma layer having transient plasma parameters (SOL plasma) and the surface of vacuum chamber can be obtained by the transition from the circular torus to the non-circular torus under consideration. Проведены численные расчеты модели магнитной системы l=2 торсатрона с некруговым полоидальным сечением тора. Показано, что максимальная величина относительного отклонения δi≈0,2 полоидального сечения некругового тора от базисного кругового сечения приводит к уменьшению области существования замкнутых магнитных поверхностей и некоторому увеличению величины угла вращательного преобразования и пробочного отношения на центральных магнитных поверхностях. Существенно увеличилось расстояние между слоем стохастических силовых линий, т.е. между плазмой переходных параметров (SOL-плазмы) и поверхностью вакуумной камеры. Проведені чисельні розрахунки моделі магнітної системи l=2 торсатрона з некруглим полоїдальним перерізом тора. Показано, що максимальна величина відносного відхилення δi≈0,2 полоїдального перерізу некруглого тора від базисного круглого перерізу призводить до зменшення області існування замкнутих магнітних поверхонь та до збільшення величини кута обертового перетворення і величини дзеркального відношення на центральних магнітних поверхнях. Суттєво збільшилася відстань між прошарком стохастичних силових ліній, тобто між плазмою перехідних параметрів (SOL-плазмою) і поверхнею вакуумної камери.